2019
DOI: 10.1111/jdi.13164
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of adipose‐derived mesenchymal stem cell sheets directly into the kidney suppresses the progression of renal injury in a diabetic nephropathy rat model

Abstract: Aims/Introduction: Adipose-derived mesenchymal stem cell (ASC) transplantation is a promising therapy for diabetic nephropathy (DN). However, intravascular administration of ASCs is associated with low engraftment in target organs. Therefore, we considered applying the cell sheet technology to ASCs. In this study, ASC sheets were directly transplanted into the kidneys of a DN rat model, and therapeutic consequences were analyzed. Materials and Methods: Adipose-derived mesenchymal stem cells were isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 44 publications
(59 reference statements)
1
31
0
Order By: Relevance
“…Repeated intravenous injections of ad-MSCs attenuated glomerulus hypertrophy and urinary protein excretion in STZ-induced diabetic rats [58]. Moreover, Takemura et al showed that transplantation of ad-MSCs under the renal capsule of Spontaneously Diabetic Torii fatty rats attenuates glomerular and tubular injury to a greater extend compared to ad-MSCs administrated per intravenous route [59]. Finally, Lee SE et al have shown that treatment with ad-MSCs prevented albuminuria and tubular epithelial cell injury via induction of the Arginase-1, a marker of M2 macrophages, and subsequent improvement of mitochondrial function [60] Although these pre-clinical studies in DKD suggest that MSC-based therapy may represent a novel promising tool for DKD treatment, the experimental design of these studies is heterogeneous in terms of cell types, doses, administration route, diabetes duration, making it difficult to translate these findings into clinical practice.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Repeated intravenous injections of ad-MSCs attenuated glomerulus hypertrophy and urinary protein excretion in STZ-induced diabetic rats [58]. Moreover, Takemura et al showed that transplantation of ad-MSCs under the renal capsule of Spontaneously Diabetic Torii fatty rats attenuates glomerular and tubular injury to a greater extend compared to ad-MSCs administrated per intravenous route [59]. Finally, Lee SE et al have shown that treatment with ad-MSCs prevented albuminuria and tubular epithelial cell injury via induction of the Arginase-1, a marker of M2 macrophages, and subsequent improvement of mitochondrial function [60] Although these pre-clinical studies in DKD suggest that MSC-based therapy may represent a novel promising tool for DKD treatment, the experimental design of these studies is heterogeneous in terms of cell types, doses, administration route, diabetes duration, making it difficult to translate these findings into clinical practice.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Glucose was almost detected after the MSCs treatment, except for 2 studies [27,32]. Sixteen studies measured glucose for once at the end of the experiment [13-16, 18-24, 26, 28-31].…”
Section: Assessment Of Glucosementioning
confidence: 99%
“…Multiple intravenous infusion of ADSCs could attenuate in ammation, promote tissue repair and improve the prognosis of the long-term complications of T2DM [33]. Compared with intravenous injection, ADSCs sheet transplantation to the kidney had the advantage of higher e ciency [32]. Because of the importance of microvesicle, ultrasonic technology has been studied for microvesicles destruction to make them take effect easily.…”
Section: Secretion Of Tropic Factorsmentioning
confidence: 99%
“…Glucose was detected after MSC treatment in all but 2 studies [32,37]. Sixteen studies measured glucose once at the end of the experiment [18-21, 23-29, 31, 33-36].…”
Section: Assessment Of Glucosementioning
confidence: 99%